2004
DOI: 10.1111/j.1365-2044.2004.03975.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient controlled analgesia for labour: a comparison of remifentanil with pethidine*

Abstract: SummaryWe compared the analgesic efficacy and safety of remifentanil and pethidine via patient controlled analgesia for women in established uncomplicated labour. Women received either remifentanil 40 lg with a 2-min lockout (n = 20) or pethidine 15 mg with a 10-min lockout (n = 19). Visual analogue scores for pain during the study and for overall pain were similar for both groups (mean (SD) 6.4 (1.5) cm for remifentanil and 6.9 (1.7) cm for pethidine). The area under the curve for visual analogue scores of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 27 publications
3
113
0
8
Order By: Relevance
“…Similar degrees of analgesia have been shown in other studies; however, most of these studies evaluated analgesic efficacy only for the first two to three hours after initiation of PCA. [10][11][12][13][14]25 One possible explanation for an increase in pain scores towards the end of labour in our study was the practice of continuing PCA into the second stage of labour when the intensity and frequency of pain are likely to be greater. Douma et al 10 observed superior analgesia with remifentanil compared with fentanyl in labouring patients; however, the difference was evident only during the first hour of treatment, and pain scores returned to baseline values in both groups within three hours of initiation of PCA.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Similar degrees of analgesia have been shown in other studies; however, most of these studies evaluated analgesic efficacy only for the first two to three hours after initiation of PCA. [10][11][12][13][14]25 One possible explanation for an increase in pain scores towards the end of labour in our study was the practice of continuing PCA into the second stage of labour when the intensity and frequency of pain are likely to be greater. Douma et al 10 observed superior analgesia with remifentanil compared with fentanyl in labouring patients; however, the difference was evident only during the first hour of treatment, and pain scores returned to baseline values in both groups within three hours of initiation of PCA.…”
Section: Discussionmentioning
confidence: 79%
“…Our regimens for remifentanil and fentanyl were based on previous studies performed at our hospital that demonstrated effective analgesia with minimal maternal adverse effects. 15,29 Although remifentanil IVPCA has been used widely in the last decade for pain management during labour with 11,13,[15][16][17][18] or without background infusion, 6,12,14,[19][20][21] its most appropriate dosing regimen is still debated. Effective analgesia has been shown in studies that used infusions and escalating dose regimens titrated to individual patient requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the VAS expressed in millimetres is divided by 10 (making a uniform score of 0-10) and a similarity between NRS and VAS is assumed, there seems to be a fast action with reduction of pain by -0.3 to 5.4 (mean or median, depending on the original study) during the first hour of remifentanil analgesia. The slightly negative PID was observed in a setting with a fast, fixed PCA-bolus of 40 µg/kg without a background infusion (Blair et al 2005) while the largest PID was noted in a study employing a flexible PCA-bolus of 0.27-0.93µg/kg (Evron et al 2005). Unfortunately, the duration of the bolus was not reported in the latter study.…”
Section: Analgesia With Remifentanil Epidural Block and Nitrous Oxidementioning
confidence: 49%
“…Four studies have compared remifentanil with pethidine displaying a somewhat better analgesia with remifentanil (table 1). Blair et al (2005) did not observe a significant difference in pain scores between remifentanil and pethidine analgesia, however, in spite of an observable difference in overall satisfaction in favour of remifentanil.…”
Section: Analgesia With Remifentanil Epidural Block and Nitrous Oxidementioning
confidence: 66%